2016
DOI: 10.1097/acm.0000000000001137
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Perceptions of the Learning Environment at the End of the First Year: A 28-Medical School Collaborative

Abstract: At year's end, students' perceptions toward the learning environment, as reported on the MSLES, differed significantly according to the medical school campus where they trained. Further studies are needed to identify specific factors, such as grading policies, administrative support, and existence of learning communities, which may influence perceptions of the learning environment at various schools. Identifying such variables would assist schools in developing a positive learning environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 13 publications
0
32
0
2
Order By: Relevance
“…Although there could be student selection bias for schools with or without LCs, the differences in MSLES scores were likely not due to demographic characteristics because an earlier study of the LES found that the influence of student demographics on total MSLES score was small in comparison with the influence of the LE. 11 Future directions include following cohorts longitudinally to assess whether differences in perceptions of the LE between LC and non-LC schools are maintained during the clinical years. Characteristics of LCs such as funding, amount of time dedicated to LCs, and curricular versus extracurricular functions could be explored to identify factors that affect the LE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there could be student selection bias for schools with or without LCs, the differences in MSLES scores were likely not due to demographic characteristics because an earlier study of the LES found that the influence of student demographics on total MSLES score was small in comparison with the influence of the LE. 11 Future directions include following cohorts longitudinally to assess whether differences in perceptions of the LE between LC and non-LC schools are maintained during the clinical years. Characteristics of LCs such as funding, amount of time dedicated to LCs, and curricular versus extracurricular functions could be explored to identify factors that affect the LE.…”
Section: Discussionmentioning
confidence: 99%
“…The study has been previously described in detail by Skochelak et al 11 To summarize, we examined data from the preclerkship years, which were collected from the fall semester of 2010 through the spring semester of 2012 for the first cohort, and from the fall semester of 2011 through the spring semester of 2013 for the second cohort. Approval for LES collaboration was obtained from the University of Michigan Medical School institutional review board (IRB); each participating medical school received local IRB approval.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other factors belong to the personal and institutional fields. The institutional culture can influence both the educational context itself and its perception by students [51]. However, the impact of institutional factors is about four times smaller than that of individual factors on the perceptions of the educational context [52].…”
Section: Discussionmentioning
confidence: 99%